Reducing Carbon Footprints by Adopting Effective and Smart Technology Applications & Role of Green Audit - Dr. Shilpa N. Gaikwad,; Dr. Sanket Charkha,; Ms. Apurva Satpute, (The Bioscan, 2025)
Already, climate change is harming both urban and natural systems, leading to worldwide economic losses of more than $500 billion. This is a problem that AI might help with in part because it uses data from the internet to generate quick recommendations based on reliable projections of future climate change. Here we take a look back at some of the most recent developments in the field of artificial intelligence as it pertains to reducing deforestation, creating resilient cities, improving energy efficiency, transportation, grid management, building design, transportation, precision agriculture, industrial processes, and the fight against climate change. Improving energy efficiency may help mitigate climate change, according to our findings. In instance, smart manufacturing has the potential to cut building energy usage by 30–50% while also reducing waste and carbon emissions. Approximately 70% of the world's natural gas producers use AI systems to improve the precision and dependability of weather predictions. Electricity expenses may be cut by 10-20% by optimising power system efficiency with the use of smart grids and artificial intelligence. Around 60% less carbon dioxide emissions are possible with intelligent transportation systems. In addition, using AI into natural resource management and resilient city planning may have a multiplicative effect on sustainability efforts.